O império e o imperador através da viagem de Dom Pedro II à província de Pernambuco em 1859. - Costa, Ana Cristina Bezerra (2019)
This dissertation sought to identify and analyze the main reasons for the coming of D. Pedro II to the north of the country, especially for the province of Pernambuco. Studies on the Emperor's voyage and his entourage in 1859 interpret this shift as part of a political strategy to reinforce the image of the Emperor and the monarchy itself. Nevertheless, a fresh look at the sources and the fruitful dialogue with historiography allow us to evaluate the 1859 visit from the more concrete perspective of immediate political gains, complementing what has been written so far. At first, we studied Pernambuco's politics, economy and society in the late 1850s. Later, starting from publications in the main local newspapers and the court, from letters exchanged between influential Pernambuco politicians beyond the vast historiography, we examined the national political scene at Pernambuco in 1859 and the strategies adopted by the Emperor in conducting the government. Then, based on the detailed notes made by the emperor in his diary and the articles from local newspapers, we analyzed the itineraries made, the contacts maintained, the events promoted by the elite, the financial support given to the local entities as well as the awarded awards and We seek to unravel the purposes of D. Pedro II for Pernambuco that justified his removal from the Court. Finally, we suggest a visitation guide to some places traveled by the imperial entourage in Recife as support in teaching about the rituals, symbols and strategies of government of the Brazilian monarchy, especially of the Second Empire.